2003
DOI: 10.2134/agronj2003.3350
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Nitrogen Application Timing Influence on Grain Yield and Protein Concentration of Hard Red Winter and Spring Wheat

Abstract: Foliar N applications on wheat (Triticum aestivum L.) have increased grain protein. Foliar N timing evaluations have been minimal. The objectives were (i) determine the optimal timing of foliar N for increased grain protein of hard red winter wheat (HRWW) and spring wheat (HRSW), (ii) evaluate effect of foliar N on grain yield, and (iii) determine relationship of grain protein to foliar N application and grain yield. Foliar N was applied at Feekes stage 10.0 (boot) or 10.8 (postpollination) on two cultivars of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 15 publications
7
35
0
Order By: Relevance
“…Maintaining adequate N levels is important since many of the newer high‐yielding cultivars commonly have lower GPC, requiring careful N management to meet grain quality standards. Post‐pollination (three‐split) N treatment gave the highest grain protein concentration in three out of five environments and was in agreement with previous studies (Bly and Woodard, 2003; Woolfolk et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Maintaining adequate N levels is important since many of the newer high‐yielding cultivars commonly have lower GPC, requiring careful N management to meet grain quality standards. Post‐pollination (three‐split) N treatment gave the highest grain protein concentration in three out of five environments and was in agreement with previous studies (Bly and Woodard, 2003; Woolfolk et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Foliar application of N has often been used as a way to increase nitrogen use efficiency (NUE) and GPC in wheat. Bly and Woodard (2003) found post‐pollination foliar N applications increased grain protein, especially when the planned yield goal was exceeded. Schatz et al (1991) showed that postanthesis application of N increased grain protein by 0.95% points at 33.6 kg ha −1 of urea ammonium nitrate (UAN).…”
mentioning
confidence: 96%
“…It may be due to the fact that nitrogen is an essential element for growth and development and thus promotes growth and yield parameters. Similar results are also reported by Ling & Silberbush (2002), Woolfolk et al, (2002), Bly & Woodard (2003), Oko et al, (2003), Siddiqui et al, (2008) and Otteson et al, (2007Otteson et al, ( & 2008 All fertilizer treatments were significantly better than the control. In addition, high plant response to fertilization portrays the clear finger prints of integration of soil and foliar feeding.…”
Section: Effect Of N Fertilizer Treatments On Wheat Productionsupporting
confidence: 86%
“…Furthermore, the influence of a foliar N application was considered in none of these studies. Woolfolk et al (2002); Bly and Woodard (2003) and Tea et al (2004) studied the influence of a foliar N application on various quality parameters, but not on bread volume. For example Wieser and Kieffer (2001) found a strong influence of the gliadin/glutenin ratio on rheological properties and bread volume, but this could not be confirmed by Pechanek et al (1997).…”
Section: Introductionmentioning
confidence: 99%